Implementasi Model Pembelajaran Team Games Tournament (TGT) dalam Melatih Percaya Diri Mahasiswa - Zuschaiya, Diana (Fahima, 2025)
This research aims to describe the application of the Team Games Tournament (TGT) learning model in the Introduction to Islamic Studies course which focuses on increasing the self-confidence of Madrasah Ibtidaiyah Teacher Education students at Darul 'Ulum Lamongan Islamic University. The research was conducted using qualitative research methods. The data collection techniques used were interviews, observation and documentation. The research results obtained show that students' self-confidence is starting to be trained to be confident in attending lectures, this is shown by the efforts of students who are starting to dare to express the results of presentations more openly than usual (looking inferior/less confident). The activity steps include class presentations, group learning, games, competitions, next is the awards stage. Students are provided with knowledge in the form of material before discussing with the group. This stage is the initial stage of raising students' self-confidence because they receive discussion material through explanations from the lecturer. Furthermore, during discussions, each student has the opportunity to present what they understand regarding the material in their respective groups, so that students are required to practice communication and combat their feelings of inferiority. Games and competitions are a fun evaluation stage to see how far students understand the material. Apart from that, in games and matches, students will show their abilities with confidence. Appreciation or appreciation is given by the lecturer after the activity is completed. Awards are given in the form of praise, applause of appreciation, and reinforced with motivation to always increase their self-confidence. The obstacle in implementing this model is the large number of students which requires a long time, and student’s poverty. Meanwhile, the supporting category is students' motivation and interest in the learning model applied.